Advent of the virtual multidisciplinary team meeting: do remote meetings work?. Issue 10 (December 2021) - Mohamedbhai, H.; Fernando, S.; Ubhi, H.; Chana, S.; Visavadia, B.
Abstract: The multidisciplinary team (MDT) is key to the management and decision-making process for head and neck cancer. The sudden shift to virtual meetings due to the COVID-19 pandemic has been arguably the most dramatic change since inception of the MDT, and we know of no studies that have evaluated the head and neck MDT since this change in working. A preliminary questionnaire was designed and trialled, based on guidance on MDT qualities and measurable outcomes as per published national guidelines. A questionnaire was then distributed to all head and neck MDTs in the UK. We obtained 97 individual responses, from 27 units. Our results indicated that most clinicians (70.1%) felt that decision making was unchanged. Most (84.5%) also felt that technology resources were satisfactory and that some aspects of communication (viewing of images and slides) were as good or improved (76.3%). However, there were notable deficiencies with remote working. In particular, the majority of respondents perceived that engagement (43.9%), teamworking (69.1%), and training (47.7%) were worse since they moved to remote meetings. Our study suggests mixed opinions of virtual meetings. Our results demonstrate that despite remote working, head and neck MDT participants feel that they have largely been able to perform in most indicators. However, we should consider solutions to the perceived deficiencies in engagement, training, teamworking, and communication. To our knowledge, this is the first study to evaluate virtual head and neck MDT meetings, and the largest study of virtual MDTs and remote working within healthcare.